Metabolism and Endocrine Disorders: What Wnt Wrong? - Franco, Carolina N.; Noe, May M.; Albrecht, Lauren V. (Frontiers in Endocrinology, 2022)
A fundamental question in cell biology underlies how nutrients are regenerated to maintain and renew tissues. Physiologically, the canonical Wnt signaling is a vital pathway for cell growth, tissue remodeling, and organ formation; pathologically, Wnt signaling contributes to the development of myriad human diseases such as cancer. Despite being the focus of intense research, how Wnt intersects with the metabolic networks to promote tissue growth and remodeling has remained mysterious. Our understanding of metabolism has been revolutionized by technological advances in the fields of chemical biology, metabolomics, and live microscopy that have now made it possible to visualize and manipulate metabolism in living cells and tissues. The application of these toolsets to innovative model systems have propelled the Wnt field into new realms at the forefront answering the most pressing paradigms of cell metabolism in health and disease states. Elucidating the basis of Wnt signaling and metabolism in a cell-type and tissue-specific manner will provide a powerful base of knowledge for both basic biomedical fields and clinician scientists and has the promise to generate new, transformative therapies for a myriad of diseases and even processes of aging.